PTOV1 interacts with ZNF449 to promote colorectal cancer development - Zhiyong Wang; Xinwei Qiao; Kaming Xue; Qianzhi Chen; Anshu Li (Communications Biology)
Abstract PTOV1 is recognized to have a significant role in various human cancers, including prostate cancer. However, it remains unclear what its clinical significance and biological role are in colorectal cancer (CRC). TCGA, NCBI/GEO, and Kaplan–Meier plot database mining provided important clues into the function and clinical importance of PTOV1 in CRC. Western blotting, immunohistochemistry, and immunofluorescence were utilized to discover PTOV1 protein levels in CRC cell lines and tissues. To explore the involvement of PTOV1 in the development of CRC and the underlying mechanisms, several in-vitro and in-vivo studies were executed, such as CCK-8 assays, colony formation, transwell assays, qRT-PCR, Co-IP, GST pull-down, immunostaining, and mouse xenograft assays. It was shown that PTOV1 expression level was upregulated in the tissues and cells of human CRC. PTOV1 high-expression level was associated with short survival. ZNF449 interacted with PTOV1 and accelerated CRC development in vitro and in vivo. Through Co-IP and GST pull-down studies, the physical interaction of PTOV1/ZNF449 was demonstrated. Furthermore, PTOV1 directly bound ZNF449, and this complex synergistically promoted the transcription of MYC. In addition, the PTOV1/ZNF449 interaction was disrupted by the TAT- PTOV1 (125–283 aa) protein leading to inhibit the CRC development in a xenografted mouse model. According to these findings, PTOV1 has an essential role in CRC progression, and PTOV1/ZNF449 interaction could be a possible therapeutic target for CRC.